Thermally reversible cross-linked poly(ether-urethane)s - V. Gaina; C. Gaina; O. Ursache; C. D. Varganici (eXPRESS Polymer Letters)
Cross-linked poly(ether-urethane)s were prepared by Diels-Alder (DA) reaction of the furan-containing poly(ether-urethane) to bismaleimides and showed thermal reversibility evidenced by differential scanning calorimetry and attenuated total reflectance in conjunction with Fourier transform infrared spectroscopy (ATR-FTIR). The furan-containing poly(ether-urethane)s were synthesized by the polyaddition reaction of 1,6-hexamethylene diisocyanate (HMDI) or 4,4'- dibenzyl diisocyanate (DBDI) to poly(tetramethylene ether) glycol (PTMEG having Mn = 250, 650, 1000, 1500 and 2000) and 2-[N,N-bis(2-methyl-2-hydroxyethyl)amino]furfuryl as chain extender by the solution prepolymer method. The molar ratio of isocyanate: PTMEG:chain extender varied from 2:1:1 to 4:1:3, which produces a molar concentration of furyl group ranging between 3.65•10–4 and 1.25•10–3 mol/g.